2003
DOI: 10.1186/ar1019
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, autoimmunity and arthritis: Perturbations of TCR signal transduction pathways with ageing – a biochemical paradigm for the ageing immune system

Abstract: 290 APC = antigen-presenting cell; DRM = detergent-resistant microdomain; ERK = extracellular signal-regulated kinase; IFN = interferon; IL = interleukin; ITAM = immunoreceptor tyrosine-based activation motif; LAT = linker of activated T cells; mAb = monoclonal antibody; MAPK = mitogenactivated protein kinase; MHC = major histocompatibility complex; NF = nuclear factor; NFAT = nuclear factor of activated T cells; PKC = protein kinase C; pLAT, tyrosine-phosphorylated LAT; PTK = protein tyrosine kinase; RA = rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 115 publications
(126 reference statements)
2
20
0
1
Order By: Relevance
“…In other words, mice which initially have T-cell repertoires skewed towards Th1 T-cells, are likely to have lower blood (and presumably total) Aβ levels. It has been suggested that rheumatoid arthritis patients, those with chronic (Th1) inflammation, have a significantly lower risk of developing Alzheimer’s disease [67], [68]. Our results are consistent with the finding that an inclination towards a Th1 T-cell reaction may lower Aβ levels.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, mice which initially have T-cell repertoires skewed towards Th1 T-cells, are likely to have lower blood (and presumably total) Aβ levels. It has been suggested that rheumatoid arthritis patients, those with chronic (Th1) inflammation, have a significantly lower risk of developing Alzheimer’s disease [67], [68]. Our results are consistent with the finding that an inclination towards a Th1 T-cell reaction may lower Aβ levels.…”
Section: Discussionsupporting
confidence: 92%
“…2427 As younger age in MDS represents an important characteristic related to IST response, the CD4+ and CD8+ naive and memory cell populations and the CD4:CD8 ratio were compared among eight IST responders and fifteen non-responders (ages ranged from 19 to 72 years old with a mean age of 46 and 62 years among responders and non-responders, respectively) to gain a better understanding of how altered T-cell homeostasis affects bone marrow suppression among the younger cases. To understand the relationship between T-cell turnover and IST response, we also determined the expression of Ki67, a nuclear proliferation-associated antigen, as an indicator of proliferation in both the CD4+ and CD8+ T cells.…”
Section: Resultsmentioning
confidence: 99%
“…Calpain inhibition was reported to activate MAP kinases: Erk, p38, JNK, PI3K/Akt and others, but only in monocytes and not in lymphocytes [26]. Still, knowing that the kinases listed above are crucial for appropriate T cell activation [26, 46], it is conceivable that they would also be affected by calpain activity in these cells upon stimulation. On the other hand, proteolytic modulation of the same protein may result in its activation or inhibition depending of the extent and duration of calpain activity [16, 24, 47].…”
Section: Discussionmentioning
confidence: 99%